The Conservation of Native Honey Bees Is Crucial. (September 2019) - Requier, Fabrice; Garnery, Lionel; Kohl, Patrick L.; Njovu, Henry K.; Pirk, Christian W.W.; Crewe, Robin M.; Steffan-Dewenter, Ingolf
Abstract : Recent studies have emphasized the role of the western honey bee, Apis mellifera, as a managed agricultural species worldwide, but also as a potential threat to endangered wild pollinators. This has resulted in the suggestion that honey bees should be regulated in natural areas to conserve wild pollinators. We argue that this perspective fails to appreciate the multifaceted nature of honey bees as native or introduced species with either managed or wild colonies. Wild populations of A. mellifera are currently imperiled, and natural areas are critical for the conservation of local subspecies and genotypes. We propose that a differentiation between managed and wild populations is required and encourage integrated conservation planning for all endangered wild bees, including A. mellifera . Highlights: The western honey bee, Apis mellifera, is globally the most prominent pollinator used for pollination services in crops and is often known only as a domesticated species managed by beekeepers. Recent studies suggest that the presence of large numbers of introduced managed colonies can threaten wild bee populations. Therefore, proposals to exclude A. mellifera colonies from protected areas have arisen. The diversity of honey bee subspecies in Europe, Africa, and western Asia as a threatened component of the native fauna is underappreciated. In Europe, wild honey bee populations are endangered, due to lack of nesting sites and hybridization between and the transfer of pathogens and parasites from managed to wild populations. Natural areas, especially protected areas, are critical for the conservation of the wild populations of the western honey bee in its native range.